Perlindungan Pengolahan Naniura Masyarakat Batak Toba Atas Ekspresi Budaya Tradisional - Sembiring, Dias Sakti Jopa; Narwadan, Theresia Nolda Agnes; Balik, Agustina (PATTIMURA Law Study Review, 2024)
ABSTRACT: The Toba Batak region is an area that has traditional cultural expressions which are usually called naniura. Protection of the Toba Batak community's processing of naniura for traditional cultural expressions is very necessary considering that Indonesia is a legal country. However, in reality, even though the State has provided protection for traditional cultural expressions, there are still many violations or cultural claims committed by foreign nations. This writing aims to find out what form of protection the Toba Batak community's processing of naniura takes on traditional cultural expressions. The research method in this writing uses a normative juridical research type which examines positive legal provisions, legal principles and legal doctrine. In conducting this research, the author uses a statutory approach and a conceptual approach. The legislative approach is carried out by examining and analyzing statutory regulations that are relevant to the legal issue being discussed. The research results show that recording WBTB at the Ministry of Education and Culture can help protect traditional cultural expressions. This is because by recording WBTB at the Ministry of Education and Culture, it can help the Ministry of Law and Human Rights in determining traditional cultural expressions so that they can be given legal force as Communal Intellectual Property (KIK). Forms of protection for the traditional cultural expression of the Toba Batak people regarding the legal processing of naniura can be carried out using two protection models, namely defensive protection and positive protection. Recording, data integration, safeguarding, maintaining KIK, as well as the formation of regional regulations are defensive protection for the Toba Batak community's natural processing of traditional cultural expressions. The positive protection itself is contained in Government Regulation Number 56 of 2022 concerning Communal Intellectual Property.